Bone morphogenetic proteins: from structure to clinical use - Granjeiro,J.M. (2005)
Bone morphogenetic proteins (BMPs) are multi-functional growth factors belonging to the transforming growth factor ß superfamily. Family members are expressed during limb development, endochondral ossification, early fracture, and cartilage repair. The activity of BMPs was first identified in the 1960s but the proteins responsible for bone induction were unknown until the purification and cloning of human BMPs in the 1980s. To date, about 15 BMP family members have been identified and characterized. The signal triggered by BMPs is transduced through serine/threonine kinase receptors, type I and II subtypes. Three type I receptors have been shown to bind BMP ligands, namely: type IA and IB BMP receptors and type IA activin receptors. BMPs seem to be involved in the regulation of cell proliferation, survival, differentiation and apoptosis, but their hallmark is their ability to induce bone, cartilage, ligament, and tendon formation at both heterotopic and orthotopic sites. This suggests that, in the future, they may play a major role in the treatment of bone diseases. Several animal studies have illustrated the potential of BMPs to enhance spinal fusion, repair critical-size defects, accelerate union, and heal articular cartilage lesions. Difficulties in producing and purifying BMPs from bone tissue have prompted the attempts made by several laboratories, including ours, to express these proteins in the recombinant form in heterologous systems. This review focuses on BMP structure, molecular mechanisms of action and significance and potential applications in medical, dental and veterinary practice for the treatment of cartilage and bone-related diseases.